DISTRIBUSI DANA ZAKAT DAN KESEJAHTERAAN MUSTAHIQ DI BAZNAS BANYUWANGI - Subaidi Subaidi; Subyanto Subyanto (LP2M Universitas Ibrahimy, 2020)
Zakat has a very important role in improving the welfare of the society, especially the mustahiq (zakat recipients). Because zakat can consider their real needs in utilizing zakat funds for increasing welfare and reduce poverty, so that the mustahiq is expected to be a muzakki (zakat provider). But the purpose of zakat to improve mustahiq welfare is difficult to realize if there is no active role from the muzakki and zakat managers. Muzakki must be aware that their goal of zakat is not only to abort their obligations, but also to the wider interests of reducing poverty. Distribution of zakat by BAZNAS (National Zakat Agency) of Banyuwangi in improving mustahiq carried out productively by helping Mustahiq to improve welfare both individually and in groups through entrepreneurial activities that can support the economic sustainability of musatahiq. The role of BAZNAS (National Zakat Agency) of Banyuwangi in improving mustahiq welfare has been carried out by providing information for the society, especially people who are able to pay zakat (muzakki) about the importance of zakat which has great potential in assisting government programs in reducing poverty.